Change in home bias due to ghost games in the NFL - Stephan Starke; Lars Vischer; Alexander Dilger (Journal of Economics and Statistics, 2024)
We analyse changes in the National Football League (NFL) due to ghost games in 2020. The home bias disappears as expected. This also applies to semi-ghost games with significantly fewer spectators than regular games and to referee decisions regarding penalties.
Keywords: Z19; Z20; 330; American football; COVID-19; ghost games; home bias; NFL